The Little Green Data Book 2005 - World Bank (Washington, DC: World Bank, 2013)
The Little Green Data Book 2005 is based on the World Development Indicators 2005, and represents an abbreviated collection of information. Its production is a collaboration between the Development Economics Data Development Group, and the Environment Department of the World Bank. Development and poverty alleviation-the World Bank's mission-call for a long-term vision. Enhancing environmental quality, improving natural resource management, and maintaining global ecosystems are all important steps toward this goal. To achieve these lasting results we need to start from a sound base of information that helps us set priorities and measure progress toward environmental sustainability goals. The Little Green Data Book is a step in this direction, with key indicators of the environment and its relationship to people for more than 200 countries. This year's edition includes new indicators for fish catch, in the agriculture and fisheries section, and biomass fuel use, in the energy section. While there are gaps and shortcomings in the data, we hope this book will inspire decision makers at all levels to use this information and to seek to fill the gaps for their own countries. This year will be remembered for the entry into force of the Kyoto Protocol. It also marked a renewed commitment by the G-8 countries to foster development in Africa. Finally, this year will witness the reconstruction efforts following the tsunami disaster in South and East Asia.